2019
DOI: 10.3390/ijerph16091611
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Urban Quiet Areas and Perceived Restorative Benefits

Abstract: To help mitigate the adverse health impacts of environmental noise, European cities are recommended to identify urban quiet areas for preservation. Procedures for identifying urban quiet areas vary across cities and between countries, and little is known of the strength of the salutogenic (health-promoting) benefits they may provide. Taking a multi-site approach, this study examines the potential of three sites as urban quiet areas and their associated health benefits, particularly in relation to perceived res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
0
23
1
1
Order By: Relevance
“…One possible reason may be that they took children’s psychological responses as a research object. In a recent study in UK, Payne and Bruce reported that relationships between sound levels (subjective and objective) and psychological restoration were not linear, which was also different from this study [16]. It may be because the type of sounds heard and other aspects of the place experience affect the relationships.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…One possible reason may be that they took children’s psychological responses as a research object. In a recent study in UK, Payne and Bruce reported that relationships between sound levels (subjective and objective) and psychological restoration were not linear, which was also different from this study [16]. It may be because the type of sounds heard and other aspects of the place experience affect the relationships.…”
Section: Discussioncontrasting
confidence: 83%
“…In recent years, some studies have assessed the psychological recovery potential of soundscapes [8,13,14,15]. They focused on the relationship between the acoustic environment and psychological responses [16,17] and they identified the sound sources that promoted positive emotions (stress recovery) [13,18]. According to a study by Daniel Shepherd et al, the mean scores of psychological well-being described by the WHO’s short-form quality of life instrument (WHOQOL-BREF) perceived by residents in quiet areas were higher than in noisy areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…This more generally raises the point about what sound sources one would expect to contribute more to quietness perception, as well as supporting health and well-being. To some extent, the work by Payne and Bruce [8] also claims that the type of sounds heard and other aspects of a site experience are likely to be related to a non-linear relationship between sound levels and perceived restoration of an acoustic environment. Other contextual aspects might indeed play a role, such as audio-visual interactions in environmental perception, as suggested in the work by Zhang et al [9].…”
Section: Rethinking Quiet Areas and Their Restorative Potential For Hmentioning
confidence: 99%
“…To achieve these goals, a great deal of study in the field of environmental acoustics have focused on the characterization and preservation of the soundscapes of these areas [4][5][6], along with an analysis of the factors which can modulate well-being [7].…”
Section: Introductionmentioning
confidence: 99%